GAMBARAN HASIL PEMERIKSAAN SITOLOGI SERVIKS WANITA PEKERJA SEKSUAL TIDAK LANGSUNG PADA HOTSPOT X KECAMATAN PAYUNG SEKAKI PEKANBARU - Putri Deas H; Wiwit Ade Fidiawati; Amru Sofian (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is most common gynecology malignancy in the world. Cervical cance is second place in deadly high cancer on female after breast cancer. Indirect female sex workers have high risk to get cervical cancer. Pap smear screening is used to identify pracancers lesion. The number of cervical cancer cases can be reduced with Pap smear screening. The purpose of this study was to know the result of cervical smear cytology examination toward indirect female sex workers at hotspot X Payung Sekaki Pekanbaru. This study was descriptive study. The population of this study were all of indirect female sex workers at hotspot X Payung Sekaki and the samples were taken with total sampling method. The result showed that there were 31 people consist 10% diagnosed with negative intraepithelial lesion or malignancy (Bacterial vaginosis), 35% diagnosed with ASCUS and 55% diagnosed with LSIL. The conclusion is LSIL was the most common intraepithelial lesion of cervical cancer.Key words: cervical smear, Pap smear, cervical cancer, indirect female sex workers, hotspot X Payung Sekaki.